A fluorescent peptidyl substrate for visualizing peptidyl-prolyl cis/trans isomerase activity in live cells. Issue 15 (1st February 2018) - Jiang, Quan; Li, Xiao-Rong; Wang, Cheng-Kun; Cheng, Juan; Tan, Chao; Cui, Tian-Tian; Lu, Nan-Nan; James, Tony D.; Han, Feng; Li, Xin
Abstract : Imaging active PPIases in live cells with a small molecular probe. Abstract : This communication reports on a fluorescent probe (PPI-P ) for imaging active peptidyl-prolyl cis / trans isomerases in live cells.PPI-P is capable of responding to both recombinant and cellular PPIases fluorogenically, and has been shown to specifically image active PPIases in live cells.